THE INFLUENCE OF VARROASIS INVASION ON LIFE TIME OF APIS MELLIFERA L., 1758 HONEY BEE - Nazarenko, O. S. (Scientific Progress & Innovations, 2019)
The sustainable development of agriculture and improvement of food supply to the population is connect-ed with solving the problem of increasing the efficiency of agricultural production at the level of the country, region, and enterprise. An integral part of it is the development of beekeeping, which is especially important in revealing its reserves of increasing the volumes of manufacturing its products and substantiating the ways of more rational using bees in various spheres of human activity. One of the reasons hindering the develop-ment of beekeeping is invasion diseases, varroosis among them, the causal agent of which is Varroa destruc-tor Anderson & Trueman, 2000 mole mite. The research was conducted in the Laboratory of the Department of Parasitology and Veterinary-Sanitary Expert Examination at Poltava State Agrarian Academy and on a private apiary of Hrebinka district, Poltava region. According to the results of the research it was found that varroasis invasion has a negative effect on the indices of honey bee (Apis mellifera L., 1758) life activity, as well as on preserving the whole bee family, especially during the preparation of bees for winter. With the invasion intensity of one V. destructor mite per bee, the life time of the infested bees was shorter than that of the insects uninfected with mites during the entire study period. Studying the dynamics of bee life time during the season showed a gradual decrease of this index in infested bees from May to September. Thus, in the spring, the life time decreased by 20.35 % (up to 19 days) as compared with uninfected bees. The death of bees was registered beginning from the 12th day of the experiment and up to the 27th day. In the summer pe-riod, the life time of infested bees was 12.96 % shorter (up to 19 days) relative to the mite-free bees. The first cases of bee death were also established on the 12th day of the experiment, and on the 26th day 100 % of death cases were detected. During the autumn period, the life time of bees infected with mites was the short-est (up to 16 days), which is 35.24 % less than in uninfected specimens. Bee deaths began to be detected from the 11th day, and 100 % of their deaths were registered on the 24th day of the experiment.